Grandparenting and children wellbeing: The significant role of grandparents in current society. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2010)
With diversifying families, increased life expectancy, growing numbers of dual-worker households and higher rates of family breakdown, grandparents are now playing an increasing role in their grandchildren's lives. Statistics show that men and women may spend longer time in life being grandparents (average 2S years) than being parents with children responsibilities (18 years). Grandparents have always been central to provide support for families, particularly in times of need or family crisis, and there is growing evidence that grandparents today are playing an increasing role in rearing and supporting young children. As a consequence, grandparenthood and its associate roles are achieving growing prominence. Although there is considerable research on kinship care and some from the parents' perspective, there are still limited findings from the children's perspective on their involvement with their grandparents (i.e.: what grandparents 'normally' do) and how this impacts on their well-being.